Artificial Intelligence, Media and Journalism: Between a Good Servant and a Bad Master - Tomić, Boban; Bajić, Predrag Đ. (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The increasingly rapid development of tools and capabilities provided by generative artificial intelligence is influencing media and journalistic practices, with tendencies towards a drastic transformation of media structures, and even entire media ecosystems. The use of generative artificial intelligence tools in media production, as well as in other related professions, can bring significant benefits to the process of data collection, processing, fact-checking, technical refinement of text, creating headline blocks, and other segments. It can also assist in generating and promoting pre-created authentic journalistic content on social media. However, it is crucial to always keep in mind that behind everything is human input, meaning that artificial intelligence is not the creator of something entirely new but a processor based on available data and information previously stored by humans in online systems, emphasizing the ongoing essential role of humans in these processes. On the other hand, there are limitations and potential dangers concerning the infinite possibilities of misuse of artificial intelligence, necessitating a more thorough regulatory framework to govern this area. This is not only due to the potential danger of artificial intelligence surpassing humans but generally to establish order in a new human practice that exceeds previous potentials and capacities. Therefore, it is necessary to address ethical, regulatory, and self-regulatory issues, as well as media literacy.